Structure and mechanical properties characterization of Fe3O4@Co3O4/Al2O3 nanocomposite. (July 2020) - Fatmawati, E; Sunaryono, S; Hidayat, M F; Kholifah, M N; Yogihati, C I; Taufiq, A; Mufti, N
Abstract: Recently, concrete has become a preferable primary raw material in construction, compares to wood and steel. However, some concrete cannot withstand heavy load; they even easily get eroded by seawater. That comes from the cement paste material used in a concrete based building structure. There are various ways to improve cement properties; one of them is by using nanomagnetic material in its production process. This study focuses on the synthesis and characterization of Fe3 O4 @Co3 O4 /Al2 O3 (FCA) particle that can be composited with cement material to revive the compressive strength of the cement. Co3 O4 nanoparticle and Fe3 O4 @Co3 O4 /Al2 O3 nanocomposite have been successfully synthesized using coprecipitation and sol-gel methods. The Co3 O4 nanoparticle and Fe3 O4 @Co3 O4 /Al2 O3 nanocomposite with Fe3 O4 @Co3 O4 core-shell mass variation was characterized by XRD. The characterization result shows a particle size of 4.9 nm. Meanwhile, the Fe3 O4 @Co3 O4 /Al2 O3 nanocomposite morphology has been successfully characterized using SEM instrument. The Fe3 O4 @Co3 O4 /Al2 O3 nanocomposite that tends to get agglomerated is those with an average particle size of 22.9 nm. The characterization results of Shore D in Fe3 O4 @Co3 O4 /Al2 O3 nanocomposite compressive test show that a concentration increase of Fe3 O4 @Co3 O4 core-shell significantly affects the growth of nanocomposite hardness level with an optimum value of 79.8 MPa for the highest concentration ratio. Therefore, Fe3 O4 @Co3 O4 /Al2 O3 nanocomposite is a very excellent reinforcing material for cement in the construction field.